2018
DOI: 10.1101/391946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial DNA and temperature tolerance in lager yeasts

Abstract: A growing body of research suggests that the mitochondrial genome (mtDNA) is important for temperature adaptation. In the yeast genus Saccharomyces, species have diverged in temperature tolerance, driving their use in high or low temperature fermentations. Here we experimentally test the role of mtDNA in temperature tolerance in synthetic and industrial hybrids (Saccharomyces cerevisiae x Saccharomyces eubayanus, or Saccharomyces pastorianus), which cold-brew lager beer. We find that the relative temperature t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
(33 reference statements)
1
21
0
Order By: Relevance
“…The natural hybrid S. pastorianus (hybridized from S. cerevisiae and S. eubayanus ) carries the S. eubayanus mitochondria (E. Baker et al 2015; Okuno et al 2016), while other industrial hybrids of Saccharomyces species used in wine and cider production have retained S. cerevisiae mitochondrial genome (Masneuf et al 1998). It has also recently been shown that the type of mitochondria inherited affects the phenotype (Albertin et al 2013; E. P. Baker et al 2019; X. C. Li et al 2019) and the transcriptional network (Hewitt et al 2020) in hybrids. Therefore, here, each of the tetraploid hybrids constructed were also selected for different mitotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The natural hybrid S. pastorianus (hybridized from S. cerevisiae and S. eubayanus ) carries the S. eubayanus mitochondria (E. Baker et al 2015; Okuno et al 2016), while other industrial hybrids of Saccharomyces species used in wine and cider production have retained S. cerevisiae mitochondrial genome (Masneuf et al 1998). It has also recently been shown that the type of mitochondria inherited affects the phenotype (Albertin et al 2013; E. P. Baker et al 2019; X. C. Li et al 2019) and the transcriptional network (Hewitt et al 2020) in hybrids. Therefore, here, each of the tetraploid hybrids constructed were also selected for different mitotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that mtDNA has played an important role in divergence of thermal growth profiles among the Saccharomyces species, with heat tolerance evolving primarily on the lineage leading to S. cerevisiae and cold tolerance evolving primarily on the lineage leading to S. uvarum. A related study has shown these differences have had a direct impact on the domestication of lagerbrewing yeast hybrids (Baker et al 2018)…”
Section: A Non-complementation Screen For Thermosensitive Alleles Revmentioning
confidence: 99%
“…With mitochondria, previous studies have indicated that the mitochondrial genome plays an important role in yeast thermal adaptation [47][48][49] . We found that out of the 9 unstable enzymes identified with the Posterior etcGEMs (with a Tm lower than 42 °C, Fig S7), three (ATP1, HEM1 and PDB1) belonged to the mitochondrial energy metabolism.…”
Section: Discussionmentioning
confidence: 99%